Arm Sling Versus Figure of Eight for Treating Midshaft Clavicle Fracture in Adults – A Systematic Review - Arga Saputro, Teddy (Cerdika: Jurnal Ilmiah Indonesia, 2021)
Introduction: The clavicle is a long, dual-curved bone that forms the only direct link between the axial and appendicular skeletons. Clavicle fracture is the most frequent trauma of the scapular girdle, and involves the midshaft. Although the proportion managed operatively has increased in recent years, the majority (80%) occur at the midshaft are treated non-operatively. Conservative treatments (including figure of eight and arm sling) has a high union rate and good clinical outcome in majority of cases, but very few randomized studies have compared the two. Therefore, a systematic review is needed to compare between arm sling and figure of eight bandage for treat the midshaft clavicle fracture in adults. The author hopes that this systematic review can be the consideration for the better treatment in closed clavicle fracture in adults. Method: The following strategy was used terms on several journals of comparison between arm sling with figure of eight bandage for threatening midshaft clavicle fracture in adults. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used to perform the comprehensive data collection. The authors used 5 years publication date and English language to select an appropriate journal. Result: The result is presented by comparison between arm sling and figure of egiht for the treatment outcomes. The author identified 11 relevant articles about comparison between arm sling and figure of eight to treat midshaft clavicle fracture in adults. The total number of patients was 3064 samples. The articles compare about the level of pain by VAS score, level of shortening and mean time of union. Conclusion: The arm sling has better advantages for non-operative treatment to midshaft clavicle fracture in adults than figure of eight bandage. It shows from the level of pain, level of shortening and mean time of union. The arm sling treatment has less level of pain, less level of shortening and less mean time of union than figure of eight bandage.